2011
DOI: 10.1016/j.ahj.2011.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Differential impact of race and risk factors on incidence of atrial fibrillation

Abstract: Despite some common risk factors for AF being more prevalent amongst blacks, AfricanAmericans are increasingly being reported with lower prevalence and incidence of atrial fibrillation (AF) compared to Caucasians or whites. Contemporary studies have not provided a complete explanation for this apparent AF paradox in African Americans. Although many traditional and novel risk factors for AF have been identified, the role of ethnic-specific risk factors has not been examined. Whereas hypertension has been the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 72 publications
3
38
0
1
Order By: Relevance
“…8 The same results have been found in different cohorts. [22][23][24][25][26][27][28] Complementing previous studies, we now show that AAs have lower lifetime risk of AF than whites, despite higher prevalence of AF risk factors. However, notwithstanding their lower lifetime risk, still 1 in 5 AAs in ARIC were estimated to develop AF during their lifetime, certainly not a trivial figure.…”
Section: Discussionsupporting
confidence: 53%
“…8 The same results have been found in different cohorts. [22][23][24][25][26][27][28] Complementing previous studies, we now show that AAs have lower lifetime risk of AF than whites, despite higher prevalence of AF risk factors. However, notwithstanding their lower lifetime risk, still 1 in 5 AAs in ARIC were estimated to develop AF during their lifetime, certainly not a trivial figure.…”
Section: Discussionsupporting
confidence: 53%
“…While we are not aware of demonstration of such differences specifically between South Asian and white European populations, it is possible that the presence of ethnic-specific variants contribute to the relative protection of South Asians from bradycardias. Interestingly, the incidence and prevalence of atrial fibrillation (AF) has also been reported to be higher in Caucasians when compared with other ethnic groups, even when ascertainment bias has been overcome, suggesting lower susceptibility to AF in non-white ethnic groups 30. Indeed, we observed lower AF prevalence in South Asians in this report and previously in patients hospitalised with heart failure 21.…”
Section: Discussionsupporting
confidence: 47%
“…13 Within the United States, the prevalence of atrial fibrillation is higher among whites than blacks, 39 even when controlling for modifiable risk factors, such as hypertension, diabetes mellitus, obesity, and tobacco use. 40 Increasing age is associated with increased risk of atrial fibrillation; specifically, the risk increases from 0.1% in those aged <55 years to 9% in those aged ≥80 years. 41 Men aged 75 to 79 years have twice the prevalence as men aged 65 to 69 years and >5× the prevalence of men aged 55 to 59 years.…”
Section: Atrial Fibrillationmentioning
confidence: 99%